2021
DOI: 10.1080/09546634.2021.1967268
|View full text |Cite
|
Sign up to set email alerts
|

Baricitinib for the treatment of atopic dermatitis

Abstract: Introduction: Atopic dermatitis is a common, chronic and recurrent inflammatory skin disease, with a prevalence of 15 to 20% in developed countries. It often appears in childhood but can last into adulthood. It negatively impacts patients, their families and society in general. Treatments are meant to reduce symptoms and prevent worsening of the disease, in association with a favorable safety profile. There is an unmet need in this area, with patients requiring new pharmacologic agents that are safe and effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
0
12
0
2
Order By: Relevance
“…IL-4 and IL-13 are known to play an important role in the pathogenesis of this condition and AD has been proven to be genetically related to IL-4 and IL-13 polymorphisms. 3 It was also reported that the keratinocytes show an appreciable decrease in filaggrin gene expression in the presence of IL-4 and IL-13. 17 STAT pathway is critical to mediating the effect of several key cytokines that bind to immune cells, keratinocytes and peripheral sensory neurons to propagate inflammation and itch.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…IL-4 and IL-13 are known to play an important role in the pathogenesis of this condition and AD has been proven to be genetically related to IL-4 and IL-13 polymorphisms. 3 It was also reported that the keratinocytes show an appreciable decrease in filaggrin gene expression in the presence of IL-4 and IL-13. 17 STAT pathway is critical to mediating the effect of several key cytokines that bind to immune cells, keratinocytes and peripheral sensory neurons to propagate inflammation and itch.…”
Section: Discussionmentioning
confidence: 94%
“…19 Baricitinib is a small-molecule, competitive inhibitor of the JAK family, with the chemical formula of C 16 H 17 N 7 O 2 S and a molecular weight of 371.42 g/mol. 3 Baricitinib selectively and reversibly inhibits JAK1 and JAK2, targeting the ATPase of JAK, which blocks the intracellular transmission of cytokines through the JAK-STAT pathway. 20 Baricitinib was approved by Food and Drugs Administration (FDA) for adult moderate-to-severe rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Большинство симптомов АтД появляется в течение первого года жизни, это занимает примерно 60% случаев. В 30% случаев первые симптомы АтД появятся в период между первым и пятым годами жизни и в 10% случаев после шестого года жизни [1]. Однако заболевание может проявиться уже и у взрослого.…”
Section: Introductionunclassified
“…Благодаря своей химический структуре и размеру барицитиниб может вводиться перорально, метаболизируясь в печени, быстро достигает максимальной концентрации в плазме (C max = ~94-112 нМ (4 мг 1 р/сут) в течение 1,5 ч после приема, выведение происходит в основном за счет почечной экскреции (в среднем 64,1% препарата выводится в неизмененном виде с мочой) 1 .…”
Section: Introductionunclassified